Intelligence(S), Abilities and Competencies - Paunov, Marin (Research Papers, 2009)
This study uses a combined historical and methodological approach to analyse the issue of intelligence, abilities and competencies, as well as the links between them. The text covers both the development of intelligence conceptual structures during the recent years, and the direct influence they have on the far more pragmatic objectives of management as a whole, and of Human resources management – in particular. The formation and developments of the most influential schools of thought in this respect is taken into consideration and a new and adequate understanding of these major human characteristics has been elaborated.